(untitled) (Human Factors in Design, 2023)
This work is an experience report in assisting a deafblind student. The objective is to present the teaching/learning process with assistive communication resources that overcome the difficulties encountered by the teacher. The need for students to understand the chronological division of time led to research that led to the construction of tactile calendars so that they could have access to this knowledge. The methodology used is based on the teacher’s experience report, resulting in successful procedural appropriation by the student, proving that mediation, through these resources, contributed to the education of deafblind people.